MENATA KEMBALI PRINSIP RESTORATIVE JUSTICE DALAM SISTEM PERADILAN PIDANA INDONESIA: SEBUAH GAGASAN MENCAPAI IDEALITAS - Arsyad, Yusna; M. Wantu, Fence; Ismail, Dian Ekawaty (jurnal.unprimdn.ac.id, 2023)
The purpose of this research is twofold: first, to provide a conceptualization of restorative justice principles in Indonesia's criminal justice system; and second, to examine the problematic application of these concepts in that system. Normative legal research, specifically the statutory technique and the conceptual approach, are utilized in this study piece. On top of that, the processed legal materials were analyzed using a qualitative analytical method that relies on interpretation. According to this study's findings, the judicial subsystem in Indonesia, which includes the police, the prosecutor's office, and the Supreme Court, has started to implement the notion of restorative justice. Due to the lack of a legislation governing the implementation of restorative justice in Indonesia, institutional or partial rules and guidelines continue to be used when discussing its application. This brings up the issue of sub-system authority imbalance in the criminal justice system, as well as the lack of consistent guidelines for each sub-system to apply restorative justice. As a result, the various proportional institutions within each sub-system face legal uncertainty. Thus, in order to establish legal clarity on the implementation of restorative justice, Indonesia has to enact legislation that specifically addresses this concept, known as RKUHAP.